Erythrocyte-encapsulated asparaginase (eryaspase) combined with chemotherapy in second-line treatment of advanced pancreatic cancer: An open-label, randomized Phase IIb trial. (January 2020) - Hammel, Pascal; Fabienne, Portales; Mineur, Laurent; Metges, Jean-Philippe; Andre, Thierry; De La Fouchardiere, Christelle; Louvet, Christophe; El Hajbi, Farid; Faroux, Roger; Guimbaud, Rosine; Tougeron, David; Bouche, Olivier; et al.
Abstract: Purpose: This Phase IIb (NCT02195180) open-label study evaluated erythrocyte-encapsulated asparaginase (eryaspase) in combination with chemotherapy in second-line advanced pancreatic adenocarcinoma. Methods: Eligible patients were randomized 2:1 to either eryaspase in combination with gemcitabine or mFOLFOX6 (eryaspase arm), or to gemcitabine or mFOLFOX6 alone (control arm). Co-primary endpoints were overall survival (OS) and progression-free survival (PFS) in patients with low asparagine synthetase (ASNS) expression. Secondary endpoints included OS and PFS in the entire population. Results: 141 patients were randomized (eryaspase arm, n = 95; control arm, n = 46). Median OS and PFS in patients with low ASNS expression were 6.2 months (95% CI, 5.1–8.8) in the eryaspase arm versus 4.9 months (3.1–7.1) in the control arm (HR, 0.63; 95% CI, 0.39–1.01; P  = 0.056) and 2.0 months (95% CI, 1.8–3.4) in the eryaspase arm versus 1.8 months (1.4–3.8) in the control arm (HR, 0.67; 95% CI, 0.40–1.12; P  = 0.127), respectively. In the entire population, median OS and PFS for the eryaspase arm versus control were 6.0 months versus 4.4 months (HR, 0.60; P  = 0.008) and 2.0 months versus 1.6 months (HR, 0.56; 95% CI, 0.37–0.84; P  = 0.005), respectively. The combination of eryaspase and chemotherapy was well tolerated. The most frequent Grade 3/4 adverse events in the eryaspase arm (n = 93) were gamma-glutamyltransferase increase (16 [17.2%]), neutropenia (12 [12.9%]), and physical health deterioration (12 [12.9%]). Conclusion: Eryaspase in combination with chemotherapy is associated with improvements in OS and PFS, irrespective of ASNS expression in second-line advanced pancreatic adenocarcinoma. A Phase III trial is underway. Highlights: Eryaspase provides encapsulated asparaginase within erythrocytes to minimize toxicity. Asparagine synthetase (ASNS) appears to be a prognostic indicator of pancreatic cancer. Eryaspase plus chemotherapy improved patient survival, irrespective of ASNS expression.